Core Outcome Measures for Palliative and End-of-Life Research After Severe Stroke: Mixed-Method Delphi Study. Issue 11 (16th July 2021) - Mason, Bruce; Boyd, Kirsty; Doubal, Fergus; Barber, Mark; Brady, Marian; Cowey, Eileen; Visvanathan, Akila; Lewis, Steff; Gallacher, Katie; Morton, Sarah; Mead, Gillian E.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Stroke is the second commonest cause of death worldwide and a leading cause of severe disability, yet there are no published trials of palliative care in stroke. To design and evaluate palliative care interventions for people with stroke, researchers need to know what measurable outcomes matter most to patients and families, stroke professionals, and other service providers. Methods: A multidisciplinary steering group of professionals and laypeople managed the study. We synthesized recommendations from respected United Kingdom and international consensus documents to generate a list of outcome domains and then performed a rapid scoping literature review to identify potential outcome measures for use in future trials of palliative care after stroke. We then completed a 3-round, online Delphi survey of professionals, and service users to build consensus about outcome domains and outcome measures. Finally, we held a stakeholder workshop to review and finalize this consensus. Results: We generated a list of 36 different outcome domains from 4 key policy documents. The rapid scoping review identified 43 potential outcome measures that were used to create a shortlist of 16 measures. The 36 outcome domains and 16 measures were presented to a Delphi panel of diverse healthcare professionals and lay service users. Of 48 panelists invited to take part, 28 completed all 3 rounds. Shared decision-making and quality of life were selected as the most important outcome domains for future trials of palliative care in stroke. Additional comments highlighted the need for outcomes to be feasible, measurable, and relevant beyond the initial, acute phase of stroke. The stakeholder workshop endorsed these results. Conclusions: Future trials of palliative care after stroke should include pragmatic outcome measures, applicable to the evolving patient and family experiences after stroke and be inclusive of shared decision-making and quality of life.